Islamic Banking and Microfinance Product Mechanism - Dr.Syed Abrar Hussain Shah; Prof. Dr Altaf Hussain Langrial; Dr.Hafiz Muhammad Hasan Mahmood (International Research Journal of Arabic and Islamic Studies, 2024)
Islamic banking and microfinance provide financial services that align with Shariah principles, emphasizing ethical and socially responsible financial transactions. Islamic banking prohibits interest (riba) and speculative transactions (gharar), instead focusing on profit-sharing models, asset-backed financing, and risk-sharing structures. Key Islamic banking mechanisms include Murabaha (cost-plus financing), Mudarabah (profit-sharing), Musharakah (joint venture), and Ijara (leasing). These models enable banks to earn returns while adhering to ethical and risk-averse principles. Microfinance in Islamic finance aims to support financially excluded individuals, especially in underdeveloped regions, by offering small-scale, interest-free financing and Shariah-compliant services. Islamic microfinance products often employ Qard Hasan (benevolent loans) and partnerships like Mudarabah and Musharakah, enabling low-income clients to engage in small business activities, improve livelihoods, and achieve financial independence. Overall, Islamic banking and microfinance mechanisms are distinctively designed to promote economic growth and financial inclusion within ethical frameworks, creating a sustainable alternative to conventional banking systems for underserved communities.